THE CORRELATION BETWEEN STUDENTS' GRAMMAR MASTERY AND THEIR GRAMMATICAL ACCURACY IN SPEAKING - Risalatus Sa'adah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
English is an international language that most widely used language by people in the world in both oral and written communication. For English language learners, speaking is the most crucial skill among the other skills. Students who have strong oral communication, they can participate easily in the second language environment. To have credibility in speaking, students have to study the components of target language, in this case English language. Among the components of speaking, grammar is the most important component in speaking. It means by having good grammar students can speak in clear and effective manner since grammar is the rule of language and how the sentences constructed.This research was a correlational study, conducted in June 2019 at the English education department of Faculty of Teacher Training and Education of University of Islam Malang. The sample of this research was one class which consisting 31 students. The researcher took class C because the researcher got an advise from the lecturer to choose this class. There were two instruments used in collecting data, they are TOEFL test and interview questions The data were analyzed by using Pearson Product Moment Formula in IBM SPSS version 20.The finding of this research indicated that there is no significant correlation between the students’ grammar mastery and their grammatical accuracy in speaking . It can be concluded that students who master the grammar well do not guarantee they can speak English accurately. Based on the finding of this research, it is addressed to the English lecturers to concern more in other techniques and ways of teaching grammatical accuracy in speaking English in easy way, so that the students are able to perform speaking better and accurate. It is also suggested to the further researcher to investigate large scale of subject, variable and use different instrument in order to make the result more accurate. Key Words: Grammar Mastery, Speaking Accuracy